IMPROVING THE COMPETENCE OF INDONESIAN LANGUAGE TEACHERS THROUGH THE USE OF THE JUNIOR HIGH SCHOOL LEARNING COMMUNITY (KOMBEL) IN SOPPENG REGENCY - Asfiati; M. Agus; Paida, Andi (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to describe the implementation of the learning community (Kombel) at the junior high school level in Soppeng Regency, its use in improving the competence of Indonesian teachers, and the factors that affect the utilization. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and questionnaires. The data obtained was analyzed holistically to reveal the implementation and impact of Kombel on improving teacher professionalism. The results of the study show that the implementation of Kombel at the junior high school level in Soppeng Regency has run optimally in accordance with the principles of the Independent Curriculum. The use of Kombel has proven to be effective in improving the pedagogic competence of Indonesian teachers, especially in the aspects of planning, implementation, and evaluation of learning. In addition, Kombel is a collaborative medium that supports the exchange of good practices between teachers, helps solve student learning problems, and supports the selection of relevant strategies, approaches, and methods. The factors that affect the use of Kombel include: teacher commitment and motivation, time management, availability of facilities, openness, and support from various parties. These findings affirm the importance of strengthening the learning community as a strategy to improve the quality of teacher competence in a sustainable manner.